The Effectiveness of E-Learning in English Language Teaching for Islamic Education Students: Research and Development Stages in the ADDIE Model in Islamic Higher Education - Waldan, Raziki; Wardah, Wardah; Abdullah, Johari bin (IAIN Pontianak, 2024)
This study aims to evaluate the effectiveness of using E-Learning in English language Teaching for Islamic Education Students at the State Islamic Institute (IAIN) Pontianak. The use of information and communication technology, particularly E-Learning, has become increasingly important in efforts to enhance the quality of education in higher education, including in English language instruction. This research employs a Research and Development (RD) methodology with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The findings suggest that the development of E-Learning-based instructional materials has the potential to increase students' motivation, enrich learning resources, and facilitate more effective interaction between lecturers and students, both in face-to-face and non-face-to-face settings. However, the evaluation results indicate that while the instructional materials are relevant to the learning needs and show potential for improving students' understanding and English language skills, the overall effectiveness needs further validation. Data from the evaluation section shows that certain aspects of the materials, particularly in terms of user-friendliness and long-term engagement, require improvement to fully achieve the desired learning outcomes. Therefore, while this research contributes to the improvement of English language teaching for Islamic Education Students at IAIN Pontianak, the results should be interpreted with caution, and further refinement of the materials is necessary. utilizing E-Learning, learning can become more flexible and accessible anytime and anywhere, thus supporting the achievement of students' competencies more optimally, provided that the materials undergo further development based on the feedback from evaluations.